Understanding patient empowerment along the hearing health journey. (1st February 2022) - Gotowiec, Sarah; Larsson, Josefina; Incerti, Paola; Young, Taegan; Smeds, Karolina; Wolters, Florian; Herrlin, Petra; Ferguson, Melanie
Abstract: Objective: Related to the hearing health journey, this study aimed to: (i) explore how empowerment manifests itself from individuals' first awareness of hearing loss through to hearing aid fitting and then to becoming an active hearing aid user, (ii) identify points when the different dimensions of empowerment are most relevant, and (iii) conceptualise empowerment. Design: A semi-structured interview study was conducted, followed by a template analysis of the data. Study sample: Adult hearing aid users from Sweden ( n = 8) and Australia ( n = 10) who had worn hearing aids for between 6 and 36 months. Results: The themes that emerged from the transcripts were knowledge, skills and strategies, participation, self-efficacy, and control. Conclusions: This study conceptualises empowerment along the hearing health journey as the process through which individuals with hearing-related challenges acquire and use knowledge, skills, and strategies, and increase self-efficacy, participation, and the feeling of control of their hearing health care, hearing solutions, and everyday lives. There are not specific points along the hearing health journey where any dimension is uniquely relevant, instead, each dimension is a dynamic component at all stages.